Implementasi Algoritma A* (A-Star) untuk Mencari Rute Terpendek dari Kelurahan Cibubur ke Perpustakaan Nasional Republik Indonesia - Damayanti, Yulia; Akbar, Yuma (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Traffic congestion is a major challenge in Indonesia's big cities, including Jakarta, causing unpredictable travel times, increased pollution and reduced quality of life. The causes of traffic jams in Jakarta include limited road infrastructure, an increase in the number of vehicles, and disorderly driver behavior. One solution is to utilize available alternative routes to reduce congestion and provide more efficient travel options. The National Library of the Republic of Indonesia in Jakarta, although it provides complete facilities to support learning and research activities, is often difficult to access due to traffic jams. Travel from the outskirts of cities such as Cibubur to the city center can be hampered by traffic jams at certain points. Therefore, an effective method is needed to find the closest and fastest route. The A* algorithm is an optimal and efficient route finding algorithm, often used in navigation and route planning. Implementation of the A* algorithm can help drivers find the fastest and shortest routes, reduce travel time, save fuel, and increase transportation efficiency. The research results show that of the three routes studied (Jl. Raya Bogor, Jl. DI Pandjaitan, and Jl. H.R. Rasuna Said), the DI Pandjaitan route is the fastest route with a distance of 1,561.5 km. The implementation of the A* method is expected to help find community routes quickly and overcome congestion problems and lack of knowledge about alternative routes.